1997
DOI: 10.1182/blood.v89.6.1886
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase-Associated Lipid Abnormalities in Children With Acute Lymphoblastic Leukemia

Abstract: To further elucidate the incidence and potential mechanism of asparaginase-associated lipid abnormalities in children with acute lymphoblastic leukemia (ALL), we serially obtained fasting lipid and lipoprotein studies on 38 of the 43 consecutively diagnosed children with ALL before, during, and after asparaginase therapy. We also evaluated a second population of 30 long-term survivors of childhood ALL; a fasting lipid and lipoprotein profile was obtained once at study entry. The mean peak triglyceride level du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
132
4
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(149 citation statements)
references
References 24 publications
12
132
4
1
Order By: Relevance
“…Dyslipidemia had a different pattern during therapy than the other MS components, as it was surprisingly common at the start of maintenance therapy but largely resolved during the maintenance courses that followed. This observation was most common in patients with high-risk disease and is likely related to PEGasparaginase received during the preceding course of delayed intensification [22]. However, more follow-up for dyslipidemia is required in the long-term survivorship period; after 1 year of maintenance therapy, the prevalence of low HDL was still significantly elevated at 29.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia had a different pattern during therapy than the other MS components, as it was surprisingly common at the start of maintenance therapy but largely resolved during the maintenance courses that followed. This observation was most common in patients with high-risk disease and is likely related to PEGasparaginase received during the preceding course of delayed intensification [22]. However, more follow-up for dyslipidemia is required in the long-term survivorship period; after 1 year of maintenance therapy, the prevalence of low HDL was still significantly elevated at 29.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports confirm that the administration of asparaginase, as monotherapy or in combination with prednisone, is associated with lipid abnormalities in children receiving treatment for ALL. Parsons et al (1997) reported 67% of incidence of hypertriglyceridemia and 19% with levels greater than 1000 mg/dl. It has been suggested that it may be related to an increase in endogeneous hepatic synthesis of very-lowdensity lipoprotein or decreased enzymatic activity of lipoprotein lipase that is a key enzyme in the removal of triglycerides from plasma (Hoogerbrugge, Jansen & Hoogerbrugge, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia (HTG) during L-asparaginase treatment is a known adverse event. 10 It has been suggested that it is related to an increase in the endogenous hepatic synthesis of very low-density lipoprotein. Another reason may be decreased activity in lipoprotein lipase, an enzyme involved in the removal of triglyceride-rich lipoproteins from the plasma.…”
Section: Introductionmentioning
confidence: 99%